High‐Speed Atomic Force Microscopy: Large‐Range HS‐AFM Imaging of DNA Self‐Assembly through In Situ Data‐Driven Control (Small Methods 7/2019). Issue 7 (8th July 2019) - Nievergelt, Adrian P.; Kammer, Christoph; Brillard, Charlène; Kurisinkal, Eva; Bastings, Maartje M. C.; Karimi, Alireza; Fantner, Georg E.
Abstract : In article number 1900031 by Georg E. Fantner and co‐workers, a robust controller design in atomic force microscopy, relying on optimization and experimental data, is able to identify and correct the resonances that appear when imaging at high speed, even in a liquid environment. This technology is used to record in real time the self‐assembly of blunt‐end DNA tripods into large hexagonal lattices.